Primary hyperaldosteronism is associated with increased mortality and morbidity in patients with hypertension and diabetes - Pillai, Krishnadev; Fares, Ahmed; Dargham, Soha; Al Suwaidi, Jassim; Jayyousi, Amin; Abi Khalil, Charbel (Frontiers in Endocrinology, 2023)
Aims Primary hyperaldosteronism (PA) is a common cause of hypertension. It is more prevalent in patients with diabetes. We assessed the cardiovascular impact of PA in patients with established hypertension and diabetes. Methods Data from the National Inpatient Sample (2008-2016) was used to identify adults with PA with hypertension and diabetes comorbidities and then compared to non-PA patients. The primary outcome was in-hospital death. Secondary outcomes included ischemic stroke, hemorrhagic stroke, acute renal failure, atrial fibrillation, and acute heart failure. Results A total of 48,434,503 patients with hypertension and diabetes were included in the analysis, of whom 12,850 (0.03%) were diagnosed with primary hyperaldosteronism (PA). Compared to patients with hypertension and diabetes but no PA, those with PA were more likely to be younger [63(13) vs. 67 (14), male (57.1% vs. 48.3%), and African-Americans (32% vs. 18.5%) (p<0.001 for all). PA was associated with a higher risk of mortality (adjusted OR 1.076 [1.076-1.077]), ischemic stroke [adjusted OR 1.049 (1.049-1.05)], hemorrhagic stroke [adjusted OR 1.05 (1.05-1.051)], acute renal failure [adjusted OR 1.058 (1.058-1.058)], acute heart failure [OR 1.104 (1.104-1.104)], and atrial fibrillation [adjusted OR 1.034 (1.033-1.034)]. As expected, older age and underlying cardiovascular disease were the strongest predictors of mortality. However, the female gender conferred protection [OR 0.889 (0.886-0.892]. Conclusion Primary hyperaldosteronism in patients with hypertension and diabetes is associated with increased mortality and morbidity.